Bioactive Properties of Syzygium cumini (L.) Skeels Pulp and Seed Phenolic Extracts - Santos, Catarina A.; Almeida, Felipe A.; Quecán, Beatriz X. V.; Pereira, Patricia A. P.; Gandra, Kelly M. B.; Cunha, Luciana R.; Pinto, Uelinton M. (Frontiers in Microbiology, 2020)
The emergence of bacterial strains resistant to different antibiotics has prompted the search for new sources of antimicrobial compounds. Studies have shown that jambolan (Syzygium cumini (L.) Skeels), a tropical fruit from the Mirtaceae family, has a great variety of phytochemical compounds with high antioxidant and antimicrobial activity. This study aimed to determine the centesimal composition and physicochemical characteristics of the pulp and seed of S. cumini (L.) Skeels, as well as the content of total phenolic compounds, antioxidant, antibacterial, antibiofilm and anti-quorum sensing (QS) activities of the phenolic extracts obtained from the pulp and the seeds of this fruit. The in vitro antibacterial and anti-QS activities of active films incorporated with phenolic extracts were also evaluated. Additionally, we performed molecular docking of phenolic compounds present in jambolan with the CviR QS regulator of Chromobacterium violaceum. The composition and physicochemical characteristics of the samples presented similar values to those found for the species. However, the seed phenolic extract had a higher content of phenolic compounds as well as antioxidant activity than the pulp. Both phenolic extracts presented antibacterial activity against Aeromonas hydrophila, C. violaceum, Escherichia coli, Pseudomonas aeruginosa, Salmonella enterica serovar Typhimurium, Serratia marcescens, Listeria monocytogenes and Staphylococcus aureus. The seed phenolic extract was particularly inhibitory against S. aureus. The pulp phenolic extract inhibited swarming motility and biofilm formation of A. hydrophila, E. coli and S. marcescens in sub-MIC concentrations. The pulp and seed phenolic extracts inhibited violacein production in C. violaceum. Films incorporated with both phenolic extracts inhibited the growth of bacteria, particularly Pseudomonas fluorescens, L. monocytogenes and S. aureus, as well as QS in C. violaceum. Molecular docking showed that a variety of compounds found in pulp and seed extracts of jambolan potentially bind CviR protein and may interfere with QS, particularly chlorogenic acid and dihydroquercetin. Our results indicate that pulp and seed of jambolan are good sources of antibacterial, antibiofilm and anti-QS compounds that can be used in the development of natural preservatives and application in antibacterial active films.